Thermal evolution of MnxOy nanofibres as catalysts for the oxygen reduction reaction. Issue 42 (19th October 2017) - Delmondo, L.; Muñoz-Tabares, J. A.; Sacco, A.; Garino, N.; Massaglia, G.; Castellino, M.; Salvador, G. P.; Pirri, C. F.; Quaglio, M.; Chiodoni, A.
Abstract : The present study shows how, starting from green and low-cost precursors, nanostructured manganese oxides with good catalytic efficiencies for the oxygen reduction reaction can be fabricated through the electrospinning technique. The role of the crystalline phase and morphological features, on the electro-catalytic behaviour, is discussed. Abstract : Manganese oxides (Mn x O y ) are considered as a promising catalyst alternative to platinum in fuel cell applications. In fact, a proper catalyst is needed in order to facilitate the oxygen reduction reaction (ORR) at the cathode, and platinum is considered the best material due to its low overpotential for this reaction. Contrary to platinum, Mn x O y is inexpensive, environmentally friendly and can be shaped into several nanostructures; furthermore, most of them show significant electro-catalytic performance. Several strategies have been carried out in order to increase their efficiency, by preparing light and high-surface area materials. In this framework, nanofibres are among the most promising nanostructures that can be used for this purpose. In this work, a study of the thermal, morphological and catalytic behavior of Mn x O y nanofibres obtained through the electrospinning technique is proposed. Emphasis is given to the thermal evolution of the precursors, proposing a possible crystallization mechanism of the different manganese oxides obtained. It turns out that manganese oxide nanofibres exhibit good catalytic performance for the ORR, comparable to those obtained by using Pt-based catalysts.